Analysis of the production and ceramic tradition in the Ichimay Wari artisan neighborhood, Lurin, Peru - Cáceres Hurtado, Milenka (2020)
The pottery tradition in Ichimay Wari, Lurín, Peru is analyzed and described, with the aim of proposing actions that allow its safeguarding; based on the research «Analysis of the impact of mass production on the ceramic tradition of the Ichimay Wari community, Lurín, 2018» (Cáceres, 2019). The results confirm the importance of maintaining the ceramic tradition as it is part of the intangible cultural heritage and at the same time, it is important as a symbol of cultural identity. Since ceramics is a cultural product, it is necessary to consider certain aspects that allow its commercialization, giving it the value it deserves in the market without neglecting its identity value and the importance of each of the pieces for the artisan.